INTEGER PROGRAMMING DENGAN PENDEKATAN METODE BRANCH AND BOUND GUNA MENGOPTIMALKAN JUMLAH PRODUK DENGAN KEUNTUNGAN MAKSIMAL: “Studi Kasus pada Perusahaan Furniture PT. PUTRA JEPARA” - Sauddin, Adnan; abidin, Wahyuni; Sumarni, Kiki (Jurnal MSA (Matematika dan Statistika serta Aplikasinya), 2015)
This paper discussed about optimization of the number of products with maximum profit. PT. Putera Jepara is a company that produces furniture products with finishing processes. Problems in a furniture company usually requires an integer solution to be realistic. The method used to optimize the number of products with maximum profit was the integer programming that included methods such as Branch and Bound. Branch and Bound method is the optimal solution of linear programming which resulted in the decision variables numbers. This study aimed to analyze the amount of products, which were manufactured by PT. Putera Jepara as the furniture company with a maximum cost-owned company within the available time per month.A large number and types of products that can provide optimum gain (maximum) with a branch method is to produce as much as 2 units of wardrobe, 46 sets of dining table, 2 units of cupboard and 1 unit of chair.